JAMUR PEMBENTUK GAHARU SEBAGAI PENJAGA KELANGSUNGAN HIDUP TANAMAN GAHARU (Aquilaria sp) - Subowo, Yohanes Bernard (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Agarwood is economical important non forest timber product. The objective of thisÃ‚Â research was to obtain fungi that have ability to effectively infect and form agarwood.The fungi were isolated and selected from agarwood for effective infection studies.TenÃ‚Â isolates were successfully isolated, they were belonging to Aspergillus (JG5, JG17,KT17, JG31, JG32, JG21, JG19), Penicillium (JG4), Fusarium (JG12, JG18). FourÃ‚Â isolates were successful form effective infection and they identified as Aspergillus spÃ‚Â JG17, Aspergillus sp JG31, Aspergillus sp JG32 and Fusarium sp JG12. They producedÃ‚Â secondary metabolite. The Fusarium sp JG12 was the most effective strain producedÃ‚Â agarwood and form resin gaharu on Aquilaria beccariana after 4 months inoculation. TheÃ‚Â size of agarwood formed was 2,96 cm in length and 0,16 cm wide. It is recommendedto use this strain for effective formation of agarwood.Key words: isolation, fungi, agarwood, Fusarium